Solithromycin for community acquired pneumonia in adults - Mandal, Anirban; Sahi, Puneet Kaur (Annals of Research Hospitals; Vol 1 (April 2017): Annals of Research Hospital, 2017)
Community-acquired pneumonia (CAP) is an immense public health problem owing to its morbidity, economic burden on the society, long term effects on the quality of life, and mortality. With almost 3.5 million deaths yearly, it is one of the leading causes of death worldwide (1). Both the incidence and complication rates for CAP are greater at the extremes of age, with the overall rate in adults ranging from 5–11 cases per 1,000 persons/year, but increasing to 20 per 1,000 among those above 60 with an overall mortality rate of 8–15% (2,3).